2008
DOI: 10.1021/ol8019555
|View full text |Cite
|
Sign up to set email alerts
|

The First Synthesis of a Thioglycoside Analogue of the Immunostimulant KRN7000

Abstract: The first total synthesis of a thioglycoside analogue of KRN7000, a potential immunostimulant, is described. Two key intermediates are alpha-galactosyl thiol 4 and phytosphingosine derivative 5, which were both prepared from D-galactose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 54 publications
0
39
0
1
Order By: Relevance
“…6) showed no bioactivity (28). The synthesis of S-glycoside of 1 (α-S-GalCer, 13) with no detectable bioactivity in mice in vitro or vivo was also achieved (58,59). (34,35).…”
Section: D-2 Modification Of the Galactose-ceramide Linkagementioning
confidence: 97%
“…6) showed no bioactivity (28). The synthesis of S-glycoside of 1 (α-S-GalCer, 13) with no detectable bioactivity in mice in vitro or vivo was also achieved (58,59). (34,35).…”
Section: D-2 Modification Of the Galactose-ceramide Linkagementioning
confidence: 97%
“…8 2S,3S,4R)-2-azido-3,4-dihydroxyoctadecyl)carbamoyl)-3,4,5-tris(benzyloxy)-6-((benzyloxy)methyl) , 3H), 3.48 (brs, 1H), 3.35 (s, 1H), 3.23 (brs, 1H), 3.00 (brs, 1H), 2.32 (s, 1H), 1.66 (s, 1H), 1.54-1.50 (m, 1H), 1.42 (brs, 2H), 1.32-1.25 (m, 23H) (2S,3S,4S,5S,6S)-N-((2S,3S,4R)-2-Hexacosanamido-3,4-dihydroxyoctadecyl)-3,4,5-trihydroxy-6-(hydroxymethyl)piperidine-2-carboxamide (3)…”
Section: Benzyl (2s3s4s5s6s)-2-(((2s)-2-azido-2-((4s)-22-dimethymentioning
confidence: 99%
“…[3,4] A large number of KRN7000 analogues and related compounds have been synthesized and their activity towards NKT cell-activation has been tested. [3][4][5][6][7][8][9][10] Modifications of KRN7000 are roughly based on three modifiable parts: sugar head moiety, ceramide part, and sugar-ceramide linkage. Sugar moiety modification studies suggested that: (1) α-glycosidic bond is essential for NKT cell-stimulation activity; (2) minor changes on sugar head can result in activity loss except that C-6 position can tolerate small substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of S-glycoside analogues of natural bioactive O-glycosides has been of interest as potential glycomimetics [25][26][27]. S-Glycosides are apparently more stable in vivo than native O-glycosides and also there is the possibility that they are more immunogenic, which is relevant to vaccine development [28].…”
Section: Scheme 3 Synthesis Of 10mentioning
confidence: 99%